Local Government Strategy in Increasing Regional Original Income in North Bolaang Mongondow Regency - Aneta, Asna; Yuliyani Solihin, Dwi Indah; Tohopi, Rustam; Aneta, Yanti; Wahab Podungge, Abdul (Iapa Proceedings Conference, 2024)
This study raises the topic of the strategy to increase local revenue by the North Bolaang Mongondow Regency Government. Policy decentralization encourages the existence of local governments to be more competitive in strengthening fiscal capacity through efforts to increase Local Revenue which can be used to finance development programs that directly benefit the local commusnity, such as education, health, infrastructure, and social programs. The contribution of PAD in North Bolaang Mongondow Regency from 2016-2020 tends to increase, although in 2018 there was a slight decline but in 2019 to 2020 it increased again. The research method uses a qualitative approach. The data analysis technique used in this study is the SWOT analysis technique with a qualitative approach consisting of Strengths, Weaknesses, Opportunities, Threats. The results of the study show that: 1) The SWOT analysis shows that the strategy to increase Local Revenue (PAD) of Bolaang Mongondow Regency is in quadrant I with an emphasis on the Progressive Strategy or better known as the ST Strategy; 2) The results of the QSPM analysis show that the TAS figure for external strategic factors of 4.53 is smaller than the TAS figure for internal strategic factors of 4.56; 3) The institutional/organizational aspect of managing local revenue (PAD) has implemented an employee placement system based on expertise in carrying out their main tasks and functions in each field; 4) The Governance Aspect, electronic transactions have a significant positive impact on local revenue by increasing tax compliance, administrative efficiency, and diversification of revenue sources; 5) The Personnel Aspect, shows that education and training programs related to regional financial management are in line with those carried out by the BPKD of North Bolaang Mongondow Regency by involving its employees in functional and managerial training as well as financial training at the central and regional levels.